Comment on "The promise of microfluidic artificial lungs" by J. A. Potkay, Lab Chip, 2014, 14, 4122–4138. Issue 7 (9th March 2016) - Wagner, Georg; Kaesler, Andreas; Steinseifer, Ulrich; Schmitz-Rode, Thomas; Arens, Jutta
Abstract : This comment presents an alternative view on the feasibility and clinical application of current microfluidic artificial lungs. Abstract : This comment on an article that appeared in this journal (Potkay, Lab Chip, 2014, 14, 4122–4138) presents an alternative view on the feasibility and clinical application of current microfluidic artificial lungs.